A COMPUTER PROGAM FOR COMPUTING SISMIC WAVE REFLECTION AND TRANSMISSION COEFFICIENTS OF A SINGLE INTERFACE - Suprajitno Munadi (Scientific Contributions Oil and Gas, 1985)
Reflection and transmission properties of a single interface form the basic step in understanding and solving many problems of seismic waves propagation in multilayered media.  The computational procedure of these coefficients is an essential element for numerical modeling or simulation purposes.  A computer program for computing seismic wave reflection and transmission coefficients of a single interface has been effectively performed using the Gauss-Jordan elimination technique which is operated on a 4x 4 system of simultaneous linear equations with complex elements.  The simultaneous equations have been ar ranged in matribx from.  Elements of the matrix are obtained from the application of the boundary conditions to the solution of the seismic wave equations.  The reflection and transmission coefficients for the compressional and shear waves constitute the unknowns of the simultaneous linear equations.  Experiments using the program demonstrate the efficiency and the precislon of this procedure.